Quantification of training load, energy intake, and physiological adaptations during a rugby preseason: A case study from an Elite European Rugby Union Squad - Bradley, W. J.; Cavanagh, B. P.; Douglas, W.; Donovan, T. F.; Morton, J. P.; Close, G. L. (The Journal of Strength and Conditioning Research, 2015)
Rugby Union (RU) is a high-speed collision sport consisting of an intermittent activity profile. Given the extreme physical demands of the sport, significant emphasis is placed on players possessing high lean body mass while minimizing body fat. Anecdotally, the most significant changes in body composition are observed during the preseason; however, there are no objective data on the physiological demands and energy intake during this time. We therefore monitored 45 elite European RU players over the 10-week preseason period by assessing training load using Global Positioning System and session rate of perceived exertion (sRPE) while also assessing changes in anthropometry and physical performance. For forwards and backs, respectively, mean weekly distance covered was 9,774 m (1,404) and 11,585 m (1,810) with a total mean weekly sRPE of 3,398 (335) arbitrary units and 2,944 (410) arbitrary units. Mean daily energy intake was 14.8 MJ (1.9) and 13.3 MJ (1.9), carbohydrate (CHO) intake was 3.3 (0.7) and 4.14 (0.4) g/kg body mass, protein intake was 2.52 (0.3) and 2.59 (0.6) g/kg body mass, and fat intake was 1.0 (0.3) and 0.95 (0.3) g/kg body mass for forwards and backs, respectively. Markers of physical performance (1 repetition maximum strength, speed, and repeated sprint tests) and anthropometry (body fat and estimated lean mass) improved in all players. Interestingly, all players self-selected a "low" CHO "high" protein diet. Based on physiological improvements the training load and energy intake seems appropriate, although further research is required to evaluate if such energy intakes would also be suitable for match day performance.